(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1862)
The author describes a site in Northumberland and several similarly situated local examples. The focus of the paper is the grave goods and human remains found in a barrow. He argues that this barrow belonged to a member of a Celtic border tribe around the time of the Roman invasion, based on recognisable design elements in the urns and the style of the iron weapons.